Detection of Diarrhea Etiology Among U.S. Military Personnel During Exercise Balikatan 2014, Philippines, Using TaqMan Array Cards. Issue 11 (1st November 2016) - Lertsethtakarn, Paphavee; Nakjarung, Kaewkanya; Silapong, Sasikorn; Neesanant, Pimmnapar; Sakpaisal, Pimmada; Bodhidatta, Ladaporn; Liu, Jie; Houpt, Eric; Velasco, John Mark; Macareo, Louis R.; Swierczewski, Brett E.; Mason, Carl J.
ABSTRACT: Background: Military personnel are vulnerable to diarrhea. Diarrheal disease is common when deployed for operations or exercise in developing countries. Although diarrheal disease is transient, cumulative time lost and medical asset can have a significant impact on military operations. Currently, diagnostics of diarrheal etiology typically relies on a mixture of conventional bacteriology, enzyme-linked immunosorbent assay, and polymerase chain reaction (PCR)-based methods including real-time PCR. These methods, however, can be time and labor intensive, although the identification of diarrheal etiology needs to be informative and rapid for treatment and prevention. Real-time PCR has been increasingly used to identify pathogens. Real-time PCR panels of common diarrheal pathogens have been developed, but several diarrheal pathogens are not included in the panel. An expanded and customizable panel to detect diarrhea etiology has been developed employing TaqMan Array Card (TAC) technology. TAC performs 384 real-time PCR reactions simultaneously. As currently configured for diarrheal disease by the University of Virginia, a maximum of 8 samples can be tested simultaneously with approximately 48 target pathogens per sample including bacteria, fungi, helminths, protozoan parasites, and viruses. TAC diarrheal disease panels have been successfully applied to detect pathogens in acute diarrheal stool samples from young children in several international multicenter diarrhea studies. Methods: In this study, TAC was applied to stool samples collected under an approved human use protocol from military personnel with acute diarrhea participating in the annual joint military exercise, Balikatan, between the Republic of the Philippines and the United States in 2014. Several established pathogen-specific real-time PCR detection assays were also performed in parallel for comparative purposes. Findings: TAC was applied to 7 stool samples. Campylobacter spp. was the most common diarrheal disease pathogen detected. Results from TAC matched 5 out of 6 pathogen specific real-time PCR assays. TAC required a total of 5–6 hours to complete all the procedures from nucleic acid extraction and data analysis, whereas a minimum of 18 hours and 4 hours are required for conventional bacteriology and enzyme-linked immunosorbent assay, respectively, per pathogen. Discussion: With TAC, pathogen load can be estimated from the amount of nucleic acid present for each pathogen, which can be analyzed further to better determine pathogen attribution and to compare pathogen load between case and control samples. Unfortunately, such correlative analysis was not possible because of the limited sample size available in this study. A larger sample size is needed for further evaluation of TAC on a specific population set, including military personnel. Regardless, TAC was found to be a useful and functional diagnostic platform that is less time-consuming, easy to use with high reproducibility, and costs less per sample compared to the current typically employed methods. The successful application of TAC in acute diarrhea stool samples from a US military population in the Philippines demonstrates its versatility as a potential candidate for a next-generation diagnostics platform.